Torsion of a Subserosal Myoma Managed by Gasless Laparoendoscopic Single-Site Myomectomy with In-Bag Manual Extraction - Akihiro Takeda; Hiromi Nakamura (Case Reports in Obstetrics and Gynecology)
Acute torsion of a subserosal myoma is a rare surgical emergency that is infrequently diagnosed preoperatively. Furthermore, laparoendoscopic single-site (LESS) myomectomy with in-bag tissue extraction for the management of this disorder has not yet been described. A 43-year-old, gravida 1, para 1 woman was referred to our department due to a solid pelvic mass associated with persistent abdominal pain. A pedunculated subserosal myoma with torsion was strongly suspected based on ultrasonography and magnetic resonance imaging. Emergency LESS surgery showed that the subserosal myoma arising from the posterior uterine wall torted at its pedicle in the cul-de-sac. The twisted myoma node was excised by coagulation and cut using a LigaSure Atlas, followed by in-bag manual morcellation and extraction through an umbilical wound. The present case report emphasizes that LESS myomectomy with in-bag tissue extraction is a feasible minimally invasive surgical option for the management of subserosal myoma with torsion after a precise imaging-based diagnostic evaluation.